Decision-making : processes, behavioral influences and role in business management - Hudson, Rebecca, 1972- (Business issues, competition and entrepreneurship series., 2015)
This book examines various decision-making processes, influences and its role in business management. The chapters describe the original decision-making approach based on joint use of the multi-criteria method and the method of group preferences in business management; a discussion on the internationalization decision-making process of small-medium enterprises (SMEs); and an examination on the efficiency of computer decision support systems by developing a set of universal analytic models for increasing the efficiency of fuzzy input information processing.